Comprehensive assessment of local climate change adaptation with provision of sustainable adaptation plan in South-West Coastal region of Bangladesh: A study on Dacope Upazila, Khulna - Md. Kamrul Hasan; Md. Mizanur Rahman; Abu Nayem Md. Kayes (Progress in Disaster Science)
This paper seeks to address the methodological deficiency in assessing the adoption of climate change adaptation practices within fishing and farming communities in a coastal upazila of Khulna district, Bangladesh. The derivation of an adaptation index is elucidated, considering the weight of adaptation practices based on their effectiveness, feasibility, and sustainability, as well as the number of practices adopted by households in farming and fishing communities. From the data collected through the Focus Group Discussion, household questionnaire survey, and workshop, the average household adaptation index value was established. A total of 123 household surveys were conducted within the fishing community, alongside 125 household surveys from the farming community. Additionally, 8 focus group discussions and 8 workshops took place in Dacope upazila. Sutarkhali shows the highest adaptation index among fishing communities, while Bajua leads among farming communities. Multiple regression analysis indicated that there are 5 variables that significantly impact the adoption of climate change adaptation practices among farming communities, while 6 variables were identified for fishing communities. A sustainable climate change adaptation plan was proposed emphasizing simple access to loans, climate change training, government and non-government aid, livelihood diversification, and four implementation techniques.